2016
DOI: 10.1136/postgradmedj-2015-133876
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of HBV infection in pregnant women in Turkey between 1995 and 2015: a 20-year evaluation

Abstract: The data suggest that the prevalence of HBsAg positivity is gradually decreasing among pregnant women, while the level of HBsAg antibody seropositivity is lower than expected. HBV carrier rate increases with increasing age and gravidity. In addition to the national HBV immunisation programme, the prevention of perinatal transmission should also be prioritised to decrease the HBV pool of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(12 reference statements)
2
4
0
1
Order By: Relevance
“…Regarding the year of publication, recently published studies reported significantly lower pooled prevalence estimate of 2.252% compared to earlier studies with pooled prevalence of 6.386% ( P < 0.001). The decrease in HBsAg positivity rate among pregnant women on ANC observed in recent publications in our meta-analysis has also been reported in Turkey from a period of 2013 to 2016 [ 87 ] and from 1995 to 2015 [ 88 ]. This could be probably attributed to improved awareness of both viruses [ 68 ] as well as introduction of national immunization programs.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the year of publication, recently published studies reported significantly lower pooled prevalence estimate of 2.252% compared to earlier studies with pooled prevalence of 6.386% ( P < 0.001). The decrease in HBsAg positivity rate among pregnant women on ANC observed in recent publications in our meta-analysis has also been reported in Turkey from a period of 2013 to 2016 [ 87 ] and from 1995 to 2015 [ 88 ]. This could be probably attributed to improved awareness of both viruses [ 68 ] as well as introduction of national immunization programs.…”
Section: Discussionsupporting
confidence: 85%
“…Furuncuoğlu et al (6) support the data of Şahin et al (5) in the study of hepatitis B seroprevalance of 7605 pregnant women in three different periods of 1995-2015. HBsAg positivity was found to decrease from 2.6% to 0.8% between 1995 and 2001, while anti-HBs positivity increased from 9.5% to 17.5%.…”
supporting
confidence: 59%
“…From the same cohort of that study, we analyzed pregnant women in a separate study and found it to be 1.5% for HBsAg and 11.5% for anti-HBs. Totally, 7605 pregnant women were evaluated for the period of 20 years, from 1995 to 2015 (25). It can be seen that the HBV prevalence is lower in blood donors, probably because those who are aware of their HBV status do not apply for blood donation.…”
Section: Discussionmentioning
confidence: 99%